2016
DOI: 10.1111/evo.12952
|View full text |Cite
|
Sign up to set email alerts
|

Harvest-induced phenotypic selection in an island population of moose,Alces alces

Abstract: Empirical evidence strongly indicates that human exploitation has frequently led to rapid evolutionary changes in wild populations, yet the mechanisms involved are often poorly understood. Here, we applied a recently developed demographic framework for analyzing selection to data from a 20‐year study of a wild population of moose, Alces alces. In this population, a genetic pedigree has been established all the way back to founders. We demonstrate harvest‐induced directional selection for delayed birth dates in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 138 publications
(447 reference statements)
0
36
0
Order By: Relevance
“…Terrestrial systems provide no evidence that harvestinduced evolution aids recovery. For example, intense hunting pressure (45% a year) selected for earlier primiparity in wild boar (Sus scrofa) [50] [51]. In red deer, despite theoretical predictions to the contrary [17], age of primiparity was not affected by four decades of moderate (12 -14%) harvest in Norway [52].…”
Section: Is Harvest-induced Evolution Beneficial?mentioning
confidence: 99%
“…Terrestrial systems provide no evidence that harvestinduced evolution aids recovery. For example, intense hunting pressure (45% a year) selected for earlier primiparity in wild boar (Sus scrofa) [50] [51]. In red deer, despite theoretical predictions to the contrary [17], age of primiparity was not affected by four decades of moderate (12 -14%) harvest in Norway [52].…”
Section: Is Harvest-induced Evolution Beneficial?mentioning
confidence: 99%
“…In this study, we used 28 years of detailed life history data and genetic parentage assignment (Haanes et al 2013, Kvalnes et al 2016) from a harvested, insular population of moose Alces alces to investigate the causes and consequences of AFR in males. In almost all individuals, life histories have been monitored since birth (Saether et al 2003, Solberg et al 2007, and during the study period the population has undergone large fluctuations in age and sex structure.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent studies have shown that size-selective harvest by commercial fisheries and trophy hunting can induce evolution of heritable traits56789. Harvest-induced evolution might not be desirable as the selection induced by human exploitation can be in the opposite direction of natural selection101112.…”
mentioning
confidence: 99%